The persistence and determinants of current account balances: The implications for global rebalancing - Erica Clower; Hiro Ito (University of California, Santa Cruz Institute for International Economics (SCIIE), 2011)
This paper examines the dynamics of current account balances with particular focus on the statistical nature of the persistency of current account balances and its determinants. With the assumption that stationary current account series ensures the long-run budget constraint while countries may experience local nonstationarity in current account balances, we examine the dynamics of current account balances across a panel of 70 countries. While linear unit root tests fail to reject the null hypothesis of a unit root for a number of countries, a Markov-switching (MS)-ADF econometric framework that allows for regime switches in current account dynamics not only lead us to reject the unit root null hypothesis for a much increased number of countries, but also provide notable cross country differences in the timing and duration of stationary and locally nonstationary regimes. Armed with the structural break dates the MS-ADF testing provides, we investigate the determinants of the different degrees of current account persistence. We find that the lack of trade openness, net foreign assets, and financial development help increase the degree of current account persistence. The type of exchange rate regimes is not found to be a robust determinant of current account persistence, but fixed exchange rate regime is more likely to lead an emerging market country to enter nonstationary current account regime.
Keywords: F32; F41; 330; financial liberalization; globalization; global imbalances; capital controls; institutional development